Acronyms to know - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1988)
AGRIS: International Information System for the Agricultural Sciences and Technology AGROVOC: the multilingual thesaurus of AGRIS CARIS: Current Agricultural Research Information System PADIS: Pan African Documentation and Information System POPIN...